Innovation Africa : emerging hubs of excellence (Bingley: Emerald Group publishing Limited, 2016)
Innovation is critical to growth and development in Africa. In the context of a continent characterized by fast growing economies as well as an array of socioeconomic challenges, such as high levels of poverty and inequality, innovation in Africa must be understood in an encompassing manner. Africa needs to support the emergence of its own Silicon Valleys, but it must also foster the invention and adoption of cleaner technologies that limit respiratory illnesses, deforestation and combat climate change. This book contains a number of analytical case studies that examine the nature and origins of emerging high-end innovation hubs in Africa. These 'hubs' or ecosystems are both understudied and little known inside and outside the continent. With this analysis, the book highlights and draws lessons from some of the most promising and successful innovation cases in Africa today, exploring the key factors driving their successful emergence, growth and future prospects. Relevant for scholars, policymakers, and business leaders, the book provides both inspiration and useful policy advice that can inform strategies and concrete measures to speed up the pace of innovation in Africa today.
Includes bibliographical references and index.
Keywords: Entrepreneurship -- Africa; Technological innovations -- Africa; Technological innovations; Entrepreneurship; Technologiezentrum; Innovationsförderung; Entrepreneurship; Klein- und Mittelbetrieb; Innovationsmanagement; Africa; Afrika